If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 4)(x + 3) = 18 Reorder the terms: (4 + x)(x + 3) = 18 Reorder the terms: (4 + x)(3 + x) = 18 Multiply (4 + x) * (3 + x) (4(3 + x) + x(3 + x)) = 18 ((3 * 4 + x * 4) + x(3 + x)) = 18 ((12 + 4x) + x(3 + x)) = 18 (12 + 4x + (3 * x + x * x)) = 18 (12 + 4x + (3x + x2)) = 18 Combine like terms: 4x + 3x = 7x (12 + 7x + x2) = 18 Solving 12 + 7x + x2 = 18 Solving for variable 'x'. Reorder the terms: 12 + -18 + 7x + x2 = 18 + -18 Combine like terms: 12 + -18 = -6 -6 + 7x + x2 = 18 + -18 Combine like terms: 18 + -18 = 0 -6 + 7x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '6' to each side of the equation. -6 + 7x + 6 + x2 = 0 + 6 Reorder the terms: -6 + 6 + 7x + x2 = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 7x + x2 = 0 + 6 7x + x2 = 0 + 6 Combine like terms: 0 + 6 = 6 7x + x2 = 6 The x term is 7x. Take half its coefficient (3.5). Square it (12.25) and add it to both sides. Add '12.25' to each side of the equation. 7x + 12.25 + x2 = 6 + 12.25 Reorder the terms: 12.25 + 7x + x2 = 6 + 12.25 Combine like terms: 6 + 12.25 = 18.25 12.25 + 7x + x2 = 18.25 Factor a perfect square on the left side: (x + 3.5)(x + 3.5) = 18.25 Calculate the square root of the right side: 4.272001873 Break this problem into two subproblems by setting (x + 3.5) equal to 4.272001873 and -4.272001873.Subproblem 1
x + 3.5 = 4.272001873 Simplifying x + 3.5 = 4.272001873 Reorder the terms: 3.5 + x = 4.272001873 Solving 3.5 + x = 4.272001873 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3.5' to each side of the equation. 3.5 + -3.5 + x = 4.272001873 + -3.5 Combine like terms: 3.5 + -3.5 = 0.0 0.0 + x = 4.272001873 + -3.5 x = 4.272001873 + -3.5 Combine like terms: 4.272001873 + -3.5 = 0.772001873 x = 0.772001873 Simplifying x = 0.772001873Subproblem 2
x + 3.5 = -4.272001873 Simplifying x + 3.5 = -4.272001873 Reorder the terms: 3.5 + x = -4.272001873 Solving 3.5 + x = -4.272001873 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3.5' to each side of the equation. 3.5 + -3.5 + x = -4.272001873 + -3.5 Combine like terms: 3.5 + -3.5 = 0.0 0.0 + x = -4.272001873 + -3.5 x = -4.272001873 + -3.5 Combine like terms: -4.272001873 + -3.5 = -7.772001873 x = -7.772001873 Simplifying x = -7.772001873Solution
The solution to the problem is based on the solutions from the subproblems. x = {0.772001873, -7.772001873}
| 3x+4x=10 | | 4-3x=3.5 | | 10(x+5)=3(x+33) | | 4-3x=-15 | | 3(x-5)=57-5x | | 1000+600+6x=750+400+9x | | 2x-8=96-11x | | 15-y=13 | | 6-6k-2k= | | 2*(x+3)=8 | | 0=x^2+4x-3 | | 2(3x+4)=3x+2[3(x-1)+2] | | 1*2=2 | | 5*(x+19)= | | 2(3x+4)=3x+2[3x-10+2] | | 22+r=37 | | 2(z+1)=3z+3 | | 6y-2.1=y-2.1 | | 9x+8=48+5x | | 1200+45b=1800+60b | | 7b+5=4b+6 | | a+b=1000 | | 7+5=4+6 | | 4x=2-5x | | 3y+18=7y-6 | | 3x-4(5x-7)+5=12x-7(5+8x)+10 | | X+2x+8=8+2x+x | | 2x+3k=1 | | 3x+1=3x-2 | | 5a+13b=80000 | | 3d+4=7d+8 | | (2+y)/3=-1 |